Thermodynamic data for magnesium (potassium) phosphates - Lothenbach, Barbara; Xu, Biwan; Winnefeld, Frank (Applied geochemistry, 2019)
Magnesium potassium phosphate (MKP) cements show fast setting and high early strength. MKP cements harden in the presence of water due to the reaction of potassium dihydrogen phosphate (KH2PO4) with magnesia (MgO) resulting in the formation of mainly K-struvite (MgKPO4⋅6H2O). Other hydrates, newberyite, phosphorrösslerite, cattiite and Mg2KH(PO4)2⋅15H2O are formed as intermediate phases during hydration. This paper presents a consistent thermodynamic database for magnesium phosphate hydrates based on solubility measurements for newberyite, phosphorrösslerite, farringtonite, Mg3(PO4)2⋅4H2O, bobierrite, cattiite, K-struvite, KMgPO4⋅H2O, and Mg2KH(PO4)2⋅15H2O carried at different temperature. It was found that the formation of the different hydrates is strongly influenced by pH. Newberyite, phosphorrösslerite and Mg2KH(PO4)2⋅15H2O are intermediate phases, which form at low pH as typical at very early hydration times. As pH rises, bobierrite and cattiite may be stabilised, while at high pH K-struvite forms. The phases formed are also strongly influenced by the temperature. [Display omitted]